Midhumerus adaptation in fast-pitch softballers and the effect of throwing mechanics - Bogenschutz, E. D.; Smith, H. D.; Warden, S. J. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Throwing is a vigorous activity that generates large internal loads. There is limited evidence of the effect of these loads on bone adaptation. The aim of this study was to investigate the 1) magnitude of bone adaptation within the midshaft humerus of female fast-pitch softball players and 2) influence of throwing mechanics (windmill vs overhand throwing) on the magnitude of adaptation.